Ustadzah Oki Setiana Dewi's Personal Branding Strategy on YouTube Social Media: Impact on Increasing the Popularity and Credibility of Digital Da'wah - Munawwarah, Munawwarah; Syam, Muh. Taufiq; Nurhikmah, Nurhikmah; Hasan, Adnan (Jurnal Kajian Manajemen Dakwah, 2025)
This study aims to analyze the personal branding strategy of Ustadzah Oki Setiana Dewi on YouTube and its impact on the increase in popularity and credibility of digital da'wah. The research method used in this study is a case study with a qualitative approach, analyzing the content uploaded by Ustadzah Oki Setiana Dewi and her interactions with the audience. The results show that Ustadzah Oki Setiana Dewi’s personal branding is consciously and consistently built through various types of da'wah content relevant to everyday life, including religious lectures, routine studies, and personal vlogs. Additionally, her closeness to the audience, especially through comments, live streaming, and Q&A sessions, gives the impression that she is an approachable and empathetic figure. The impact of the personal branding built is an increase in the popularity and credibility of digital da’wah, reflected in a surge in followers and audience trust in the da’wah content shared. This study implies that consistency in building an authentic self-image and close interaction with the audience can expand the reach of digital da’wah and strengthen the credibility of da’i.